Oxidative reactions of sulfinyl dienes as an entry to functionalized carbohydrate-like products and furans. Issue 32 (9th August 2019) - Castellanos, Alejandro; Osante, Iñaki; Fernández, Jorge; Fernández de la Pradilla, Roberto; Viso, Alma
Abstract: Oxidative cleavage (OsO4 /NaIO4 ) of a monoprotected dihydroxy sulfinyl diene affords a lactol, readily transformed into a sulfinyl pyranose. Alternatively, base promoted intramolecular cyclization of a lactol derived carbamate to a bicyclic oxazolidinone followed by simple transformations leads to an amino sulfonyl pyranose. In contrast, ozonolysis of a variety of hydroxy sulfinyl dienes leads to fair yields of 3-sulfinyl furans in a single step. Graphical abstract: Image 1